Análisis Financiero a la Compañía de Transporte Pesado Santa Teresita del Pangui Transpesanter SA, del Cantón El Pangui, Períodos 2020, 2021 y 2022 - Erreyes Armijos, Jimmy Javier (2024)
Financial analysis is an essential technique for examining the financial situation and economic performance of an organization. It enables the extraction of conclusions and provides recommendations that serve as a basis for decision-making. This study has fulfilled three specific objectives. First, the vertical and horizontal analysis techniques were applied, allowing us to determine the financial structure and economic performance of the organization, identify representative and significant accounts, assess absolute and relative variations, and recognize trends and financial behaviors, along with their causes and potential consequences. Second, financial indicators were utilized to measure and evaluate the evolution of liquidity, management, solvency, and profitability. Finally, a financial report was prepared summarizing the results obtained, presenting conclusions, and offering recommendations. The study employed a quantitative and qualitative methodological approach with an analytical-descriptive research design, utilizing both scientific and deductive methods, as well as interview techniques and bibliographic research. It concludes that the financial statements of the company during the examined periods were not reasonable; the financial structure was risky with a high level of debt, there was a reduction in liquidity, which led to losses, and the company was affected by external factors and underutilization of a vehicle. This study is relevant as it will facilitate decision-making to establish a healthy financial structure and improve the economic performance of the organization.